2021
DOI: 10.1038/s41598-021-01490-1
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of rat cranial bone-derived mesenchymal stem cells promotes functional recovery in rats with spinal cord injury

Abstract: Cell-based therapy using mesenchymal stem cells (MSCs) is a novel treatment strategy for spinal cord injury (SCI). MSCs can be isolated from various tissues, and their characteristics vary based on the source. However, reports demonstrating the effect of transplanted rat cranial bone-derived MSCs (rcMSCs) on rat SCI models are lacking. In this study, we determined the effect of transplanting rcMSCs in rat SCI models. MSCs were established from collected bone marrow and cranial bones. SCI rats were established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 53 publications
(69 reference statements)
3
23
0
Order By: Relevance
“…This spurs numerous efforts to isolate and characterize MSCs from a variety of human tissues for their potential clinical applications (Pikuła et al, 2013 ; Miura, 2016 ; Van Pham et al, 2016 ; Yamada et al, 2019 ). Previous studies in our lab and others have demonstrated the neurogenic potential of CB-MSCs and their contributions to ameliorating neural injury in rat models (Abiko et al, 2018 ; Ma et al, 2019 ; Maeda et al, 2021 ). The overall goal of this study was to further investigate isolated CB-MSCs at clonal level with specific emphasis on the transdifferentiation capacity and immunoregulatory functions, which are two key features that need to be elucidated as required to move forward for the development of MSCs-based therapies.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This spurs numerous efforts to isolate and characterize MSCs from a variety of human tissues for their potential clinical applications (Pikuła et al, 2013 ; Miura, 2016 ; Van Pham et al, 2016 ; Yamada et al, 2019 ). Previous studies in our lab and others have demonstrated the neurogenic potential of CB-MSCs and their contributions to ameliorating neural injury in rat models (Abiko et al, 2018 ; Ma et al, 2019 ; Maeda et al, 2021 ). The overall goal of this study was to further investigate isolated CB-MSCs at clonal level with specific emphasis on the transdifferentiation capacity and immunoregulatory functions, which are two key features that need to be elucidated as required to move forward for the development of MSCs-based therapies.…”
Section: Discussionmentioning
confidence: 83%
“…Among all tissues, cranial bone marrow have attracted interest as a promising source of MSCs with remarkable neurogenic potential. It has been reported that intravenous transplantation of MSCs isolated from cranial bone marrow (CB-MSCs) promoted functional recovery and improved motor function in rats after ischemic stroke and spinal cord injury, respectively (Abiko et al, 2018 ; Maeda et al, 2021 ). In line with these observations, previous studies in our lab demonstrated that human CB-MSCs were highly inducible into neuron-like cells with robust expression of neural markers (Ma et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, tcMEPs must be recorded in rats with varying levels of paralysis to investigate the above correlation over a relatively short period. We also reported that the transplantation of rat bone marrow-derived mesenchymal stem cells (rbMSCs) or rat cranial bone-derived mesenchymal stem cells (rcMSCs) to rat models of acute SCI enables the observation of the course of improvement in paralysis over time [17]. This previous study further showed that the waveform of tcMEPs disappears immediately after SCI and reappears with the recovery of motor function within a short period of 28 days [17].…”
Section: Introductionmentioning
confidence: 91%
“…We also reported that the transplantation of rat bone marrow-derived mesenchymal stem cells (rbMSCs) or rat cranial bone-derived mesenchymal stem cells (rcMSCs) to rat models of acute SCI enables the observation of the course of improvement in paralysis over time [17]. This previous study further showed that the waveform of tcMEPs disappears immediately after SCI and reappears with the recovery of motor function within a short period of 28 days [17]. Based on these findings, in the present study, we examined the relationship between the longitudinal electrophysiological changes and recovery from paralysis after the transplantation of MSCs in an SCI rat model.…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, MSCs have been shown to possess regenerative capabilities, also for conditions affecting the CNS. Animal studies have revealed that MSCs can migrate toward sites of injury ( 6 ) and promote repair of myelin and neurons, thus leading to improved functional outcomes in models of central nervous diseases ( 7 , 8 ). This effect is likely mediated through different mechanisms, such as the paracrine stimulation of endogenous progenitor- and stem cells through the MSC secretome ( 9 ), mitochondria donations ( 10 ), immunomodulation ( 11 ) and transdifferentiation toward neural cell lines ( 12 ).…”
Section: Introductionmentioning
confidence: 99%